2013
DOI: 10.2903/j.efsa.2013.3487
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the assessment of the potential establishment of the apple snail in the EU

Abstract: EFSA requested the PLH Panel to review the current state of the art of the biology and ecology of apple snails, reported in this opinion, and to perform an environmental risk assessment for validation of the Plant Health environment guidance document, which will be provided in a second opinion. The Panel presents in this opinion the current state of the art of the biology of apple snails, and develops and uses a population dynamics model to assess the potential establishment of apple snails in the EU. A thorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…In EFSA PLH Panel (2013), the Panel reviewed the current state of the art of the biology and ecology of the apple snail and used a population dynamics model to assess its establishment in terms of density distribution in Europe. The Panel used these results as a starting point for performing the ERA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In EFSA PLH Panel (2013), the Panel reviewed the current state of the art of the biology and ecology of the apple snail and used a population dynamics model to assess its establishment in terms of density distribution in Europe. The Panel used these results as a starting point for performing the ERA.…”
Section: Discussionmentioning
confidence: 99%
“…In this scientific opinion the Panel uses the data on biology and ecology of the apple snail and the results of the population dynamics model, presented in EFSA PLH Panel (2013), to perform an ERA following the guiding principles detailed in the PLH ERA guidance document. This task has been performed considering the possible simplification and adjustments to the Panel's environmental risk assessment guidance document.…”
Section: Terms Of Reference As Provided By Efsamentioning
confidence: 99%
See 2 more Smart Citations
“…The favorable weather conditions, the availability of food resources (crops or macrophytes), a high reproductive potential and the lack of natural predators have contributed to its success as an invader (Damborenea and Darrigran, 2002;Joshi, 2007;Hayes et al, 2008). In consequence, this species is actually distributed in several countries of Asia and Oceania, North America (Hawaii and other states of the United States) (Rawlings et al, 2007;Hayes et al, 2008;Tran et al, 2008;Cowie and Hayes, 2012) and it was even recently reported in some regions of Spain (EFSA PLH Panel, 2013), Pakistan (Baloch et al, 2012) and Russia (Yanygina et al, 2010). The impacts of P. canaliculata are not restricted to agricultural economics, but they are also a serious concern for public health as they are a known carrier of the Rat Lung Worm (Angiostrongylus cantonensis), the causative agent of eosinophilic meningoencephalitis (Lv et al, 2009;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%